The Effectiveness Of The Application Of Audit Tools And Linked Archive System (Atlas) On The Financial Statement Audit Process (Case Study at Public Accounting Firm Hari Purnomo & Jaswadi) - Nur Rohmah, Niken; Jaswadi, Jaswadi; Indrayati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The development of information technology has significantly impacted various fields, including audit practice. A notable advancement is the ATLAS application, an electronic working paper designed to assist auditors in filling out work papers. This research aimed to examine the application of ATLAS and assess its effectiveness in the financial statement audit process at KAP Hari Purnomo & Jaswadi. Using a descriptive qualitative approach, data were collected through interviews with auditors. The findings revealed that KAP Hari Purnomo & Jaswadi had comprehensively implemented the ATLAS application, covering all stages from pre-engagement, risk assessment, and risk response to reporting. The ATLAS application proved effective, as it streamlined and facilitated auditors' work in inputting audit data. The integration of all audit stages within the ATLAS application demonstrated its efficiency and effectiveness in the financial statement audit process, making it a valuable tool for auditors at KAP Hari Purnomo & Jaswadi.